Genetic diversity and association of yield‐related traits in sesame. (17th March 2021) - Teklu, Desawi H.; Shimelis, Hussein; Tesfaye, Abush; Mashilo, Jacob
Abstract: The extent of phenotypic variation among Sesame germplasm influences the expression of economic traits and the response to selection. The objective of this study was to determine the variance components, heritability (H 2 ) and association of seed and oil yield‐related traits in Ethiopian sesame germplasm to guide breeding. One hundred sesame germplasm were evaluated under field conditions in two locations in a 10 x 10 lattice design with two replications. The findings revealed higher genotypic coefficient of variation, H 2, and genetic advance for number of primary branches (NPB), number of secondary branches (NSB), thousand seed weight (TSW), seed yield per hectare (SYH) and oil yield per hectare (OYH), suggesting high genetic gains can be achieved through selection. Higher direct effects of OYH and NSPC were recorded on SYH, while SYH, NCPP and TSW had higher direct effect on OYH. The genotypes Hirhir Kebabo Hairless‐9, Setit‐3, Orofalc ACC‐2, Hirhir Humera Sel‐6, Setit‐1 and ACC‐NS‐007(2) were found superior and the selected genotypes should promote for further field stability evaluation, which might be utilized in future sesame breeding programmes and production.